(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article talks about the importance of wrestling for society and the history of its formation. A society with increased attention to sports develops in the style of a healthy society. There are all types of sports, which serve not only physical fitness, but also spiritual development of a person. In particular, wrestling is a defense of national values and it ensures the strengthening of national pride and confidence in a bright future.